2000
DOI: 10.1785/0119990053
|View full text |Cite
|
Sign up to set email alerts
|

What Can Strong-Motion Data Tell Us about Slip-Weakening Fault-Friction Laws?

Abstract: We consider the resolution of parameters, such as strength excess, r y ‫מ‬ r o , and slip-weakening distance, d c , related to fault-constitutive properties, that may be obtained from the analysis of strong-ground motions. We show that waveform inversion of a synthetic strong-motion-data set from a hypothetical M 6.5 event resembling the 1979 Imperial Valley earthquake cannot uniquely resolve both strength excess and d c. Specifically, we use a new inversion method to find two rupture models, model A having d … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
179
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 214 publications
(199 citation statements)
references
References 67 publications
(86 reference statements)
17
179
1
Order By: Relevance
“…Dynamic source parameters are often difficult to estimate because of their strong nonlinearity [Guatteri and Spudich, 2000]. Our results suggest that ther variable initial stress or variable yield stress.…”
Section: Discussionmentioning
confidence: 72%
“…Dynamic source parameters are often difficult to estimate because of their strong nonlinearity [Guatteri and Spudich, 2000]. Our results suggest that ther variable initial stress or variable yield stress.…”
Section: Discussionmentioning
confidence: 72%
“…1). Guatteri and Spudich (2000) demonstrated that for band-limited analyses of seismic waveforms, slip weakening distance may not be determined uniquely and high frequency waves are required, which are usually difficult to be extracted from observed seismograms because of the heterogeneity of the crust. Instead, it is pointed out that seismological fracture energy can be estimated stably (Ide 2002;Tinti et al 2005b) because the seismological fracture energy is an integration quantity.…”
Section: Slip-weakening Distancementioning
confidence: 99%
“…The dynamic traction evolution is commonly inferred from kinematic rupture models with the ambition to constrain the fault constitutive behavior [Ide and Takeo, 1997;Guatteri and Spudich, 2000]. Ground motion time histories are inverted to image a kinematic rupture model.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study we aim to understand if the source time functions adopted in kinematic models can bias the retrieved dynamic parameters and partially explain the variability of D c estimates. Guatteri and Spudich [2000] also emphasized the limitations in estimating the critical slip weakening distance by modeling ground motion waveforms. In particular, they concluded that both the adoption of spatial and temporal smoothing constraints in the formulation of the inverse problem and the modeling of low-frequency seismic waves can bias the inferred values of D c .…”
Section: Introductionmentioning
confidence: 99%